THE NEW ORDER OF GENDER STUDIES IN THE QURANIC WORLDVIEW - Pambayun, Ellys Lestari (Asosiasi Dosen PTKIS Indonesia, 2021)
Abstract: Worldview is a framework of thinking or fundamental beliefs about our vision of the world and a vision of our shadow or expression in the future. The term worldview is also used in Islam to explore the reality of the world through a set of Qur'an-based and hadith-based knowledge such as al-mabda', al-nazariyat, al-tawassur al-Islamiyah, and so on. The worldview device as an important element in seeing human reality refers to the three pillars of philosophy, namely epistemology, ontology, and axiology. Epistemilogy in looking at gender metamorphoses from just a definition, a concept to a study or theory. In Islam the epistemological concept is used to look at gender in two approaches: the epistemology of the bayani (a more rational worldview based on the Quranic text in viewing gender bias) and the burhani epistemology (worldview of gender in rabbaniyah, thabat, syumul, waqi'iyah, ijabbiyah, tawazun, and tawhid). In gender ontology it is discussed in its essence or